2001
DOI: 10.1177/10778010122182433
|View full text |Cite
|
Sign up to set email alerts
|

Social Support Among Women in Methadone Treatment Who Experience Partner Violence

Abstract: This study explores types, availability, use, and satisfaction of support among women in methadone treatment who reported partner violence. It also examines the role of the woman's intimate partner in isolating her from her social network. A total of 68 women participated in 1 of 14 two-hour focus groups. The findings suggest that male dominance and control function to isolate and prevent women from accessing support needed to cope with partner violence. The participants not only felt that they had few people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
78
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 23 publications
4
78
0
1
Order By: Relevance
“…Social networks may be developed or strengthened through participation in institutionalized support groups (e.g., those provided by victim support organizations). Previous studies do not provide unequivocal suggestions with regard to the compositions of such groups and either seem to advocate homophilous peer support groups (e.g., Larance & Porter, 2004) or groups including non-victims who might serve as role models (e.g., El-Bassel, Gilbert, Rajah, Foleno, & Frye, 2001). Alternatively, for those who feel uncomfortable with expressing their emotions to strangers, promoting network building through less formal ways, such as participation in work or leisure time activities that fit the victim's interests, might already suffice to deal with domestic violence in an adaptive way.…”
Section: Discussionmentioning
confidence: 96%
“…Social networks may be developed or strengthened through participation in institutionalized support groups (e.g., those provided by victim support organizations). Previous studies do not provide unequivocal suggestions with regard to the compositions of such groups and either seem to advocate homophilous peer support groups (e.g., Larance & Porter, 2004) or groups including non-victims who might serve as role models (e.g., El-Bassel, Gilbert, Rajah, Foleno, & Frye, 2001). Alternatively, for those who feel uncomfortable with expressing their emotions to strangers, promoting network building through less formal ways, such as participation in work or leisure time activities that fit the victim's interests, might already suffice to deal with domestic violence in an adaptive way.…”
Section: Discussionmentioning
confidence: 96%
“…44,45 Given the range of issues that FSW-PWID face, including higher rates of both physical and mental health problems, drug treatment programs should identify and treat women's mental health needs, while building support structures for women in treatment. 27,46,47 To mitigate barriers related to loss of income due to regular MMTP visits, alternative treatment programs, such as Btake-home^doses, may also be beneficial for FSW-PWID populations who are already economically vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that drug-involved couples are vulnerable to high levels of stress related to poverty, underemployment, and limited social supports. 17 Further, drug use may have direct effects on sexual functioning that may hinder safer sex. For example, cocaine or other stimulants may cause hyperarousal, impulsivity, or disinhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showing that increases in power are associated with safer sexual behaviors led the authors to hypothesize that the SRPS subscales will each be inversely associated with sexual risk, that is higher scores on relationship control and decision-making dominance subscales would be associated with fewer unprotected sexual occasions. Additional factors associated with increased sexual HIV risk, including age and race/ethnicity, 29 economic dependence, [15][16][17] condom use intention, 30,31 sexual concurrency, [32][33][34] and partner abuse, [35][36][37][38] were included in the analytic model to assess the unique contribution relationship power has on unprotected sex. Findings contribute to the understanding of how multidimensional heterosexual power dynamics influence unprotected sexual behavior with particular attention to a subpopulation of women who may be at higher risk for HIV transmission.…”
Section: Introductionmentioning
confidence: 99%